Pemodelan Hubungan antara Variabel Organisasional dan Variabel Pelanggan dalam Penyampaian Layanan serta Pengaruhnya terhadap Retensi Pelanggan pada Lembaga Pendidikan Tinggi - Yuniawan, Ahyar (Universitas Brawijaya, Indonesia, 2009)
Today’s organizations, included university, are challenged to deliver quality to their customers. New paradigms in higher education development for the Indonesian should be implemented because service quality and customer satisfaction could be accomplished if the organizations were effective. Organizational effectiveness has become an importance issue lately and it has center on explanations of what makes some firms excellent, of high quality, productive, efficient, healthy, or possessing vitality – all proxies for the concept of organizational effectiveness as used in the organizational sciences literature. University has shown ambiguities for its effectiveness, such as: universities are characterized by an absence of measurable goals, little connection between acquired resources and products and ability to give fair treatment to their all constituents. The study aimed to evaluate the university effectiveness and correlate to its organizational outcomes that reflect its service effectiveness (e.g.: service quality, customer satisfaction, institutional image and reputation, customer retention) and to analyze mediating role of service quality in order to gain theoretical benefits. The study employed survey method and used proportional stratified random sampling as sampling technique. The study was a linkage research in the area of higher education which required employee/manager and customer participation to evaluate service organization effectiveness and service quality because service attributes uniqueness has brought the physical, organizational and psychological closeness of employees and customers. The study’s results were effectiveness measures and good confirmation in its correlation to customer’s variables based on holistic approach in service management; the organizational effectiveness isn’t increase institutional image, institutional reputation, service quality or customer satisfaction; in the proposed model, the role and mediation effect of service quality as integration factor between organization and customer aren’t supported; the service quality of higher education increases customer satisfaction, and in the KP-ML model, it increases customer retention; the customer satisfaction increases service quality of higher education; and in the ML-KP model, it increases customer retention; the institutional image increases customer retention; the institutional reputation increased customer retention; and the total effect of organizational effectiveness did not fairly increased customer retention.Keywords: linkage research, structural equation model, survey, organizational effectiveness, service quality, customer satisfaction, institutional image, institutional reputation, customer retention, and higher education.